The Lost Apple Plays: Performing Operation Pedro Pan - Kimberly del Busto Ramírez (Studies in 20th & 21st Century Literature, 2008)
From 1960 to 1962, more than 14,000 unaccompanied minors took flight from Cuba to the United States, establishing the largest recorded exodus in the Western Hemisphere. The displaced children and the country they left behind are often metaphorized using a popular Latin American nursery rhyme, “The Lost Apple.” Now, more than four decades later, Operation Pedro Pan persists through a revealing body of performance by and about a nation’s exiled children. The Lost Apple Plays investigates how memory, identity formation, nationhood, citizenship, and migration have been dramatized through these performances. Pulitzer Prize-winning playwright Nilo Cruz, director/actor/playwright Mario Ernesto Sánchez, singers Willy Chirino and Lissette, performance artist Ana Mendieta, sculptor María Brito, prolific dramatist Eduardo Machado, and new playwright Melinda López compose a Cuba that can be neither lost nor recovered for Pedro Pans, but remains an impenetrable illusion like the restless, liminal condition of lifelong exile.
Keywords: Cuba; theatre; United States; exodus; migration; displaced; The Lost Apple; Operation Pedro Pan; exiled children; memory; identity nationhood; citizenship; Nilo Cruz; Mario Ernesto Sánchez; Melinda López